Analysis of AI-Based Big Data for Strategic Decision-Making in E-Commerce - Oktaviani, Intan; Purawanto, Eko; Triana, Triana (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
In the current digital era, e-commerce faces significant challenges in managing and analyzing vast and complex data. Big Data presents tremendous opportunities for gaining valuable insights, but traditional analysis methods often need to be more accurate and relevant information. Artificial Intelligence (AI) emerges as an effective solution to this challenge, with its ability to deeply analyze data and identify patterns and trends that conventional methods may overlook. By leveraging AI, e-commerce companies can make faster and more accurate strategic decisions, such as optimizing marketing, managing inventory, and personalizing customer experiences. Although there are challenges in implementing this technology, such as data integration and security, the benefits of using AI in Big Data analysis are substantial. In conclusion, AI is crucial in supporting data-driven strategic decision-making in the e-commerce sector.